Antioxidants As Natural Arsenal Against Multiple Stresses In Cyanobacteria - MINU KESHERI; RICHA; RAJESHWAR P. SINHA (International Journal of Pharma and Bio Sciences, 2011)
Cyanobacteria evolved as ubiquitous photosynthetic oxygen evolving prokaryotes, which owing to their limited motility are compelled to be exposed to the extremes of environmental stress conditions including oxidative stress prevailing at their natural habitats. Cyanobacteria possess an array of protective and repair mechanisms comprising of enzymatic and non-enzymatic antioxidants as natural arsenal to alleviate the damages caused by reactive oxygen species (ROS), thereby bestowing them with high adaptability to endure the hazards of endogenous and exogenous stresses. Cyanobacteria possess immense potential for serving as a source material for the production of antioxidative enzymes and pigments in addition to their role as biofertilizers. The responses and mechanisms employed by cyanobacteria may be implemented to design strategies for understanding their metabolic and genetic plasticity for further development of technologies relevant to enhancing the stress tolerance capacity of living organisms.